Nueva distribución de Lamyctes coeculus (Brölemann, 1889) (Chilopoda: Lithobiomorpha: Henicopidae) en México - Cupul-Magaña, Fabio Germán (Instituto de Ecología, A.C., 2011)
The cosmopolitan centipede Lamyctes coeculus has been recorded from the Mexican states of Estado de México, Hidalgo, Morelos, and Veracruz. The presence of the species in Puerto Vallarta, Jalisco, is reported here for the first time. The three species of Lamyctes found in Mexico (L. coeculus, L. leon, and L. tolucanus) show differences in the antennal articles arrangement.